Early recovery following total and unicompartmental knee arthroplasty assessed using novel patient-reported measures - Strickland, LH; Rahman, A; Jenkinson, C; Pandit, HG; Murray, DW (Elsevier, 2021)
Background The early postoperative recovery period following unicompartmental (UKA) and total knee arthroplasty (TKA) is an important area for research with increasingly sensitive metrics and new technologies. This study uses 2 recently developed patient-reported scores to compare the recovery following UKA and TKA.